2018
DOI: 10.1055/s-0038-1636521
|View full text |Cite
|
Sign up to set email alerts
|

Updates on Uterine Artery Embolization

Abstract: Uterine fibroids (leiomyomas) are the most common benign neoplasm of the female pelvis and have a lifetime prevalence exceeding 80% among African American women and approaching 70% among Caucasian women. Approximately 50% of women with fibroids experience symptoms which may include menorrhagia that may result in anemia, bulk symptoms with bladder and bowel dysfunction and abdominal protrusion, dysmenorrhea, and infertility. Hysterectomy remains the most common treatment option for fibroids and concerns have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 56 publications
0
19
0
3
Order By: Relevance
“…It may be an alternative to traditional treatment, especially for women with multiple fibroids, very large fibroids, restricted operability, or a history of multiple operative procedures in the abdomen [41]. UAE has some contraindications, including viable pregnancy, active infection, and suspected uterine, cervical, or adnexal malignancy [42]. However, UAE has many advantages, such as less blood loss, shorter operative times, and shorter hospital stays [43].…”
Section: Uterine Artery Embolizationmentioning
confidence: 99%
“…It may be an alternative to traditional treatment, especially for women with multiple fibroids, very large fibroids, restricted operability, or a history of multiple operative procedures in the abdomen [41]. UAE has some contraindications, including viable pregnancy, active infection, and suspected uterine, cervical, or adnexal malignancy [42]. However, UAE has many advantages, such as less blood loss, shorter operative times, and shorter hospital stays [43].…”
Section: Uterine Artery Embolizationmentioning
confidence: 99%
“…Fibroid-related bleeding in postmenopausal women may also occur and should be very carefully diagnosed prior to UAE. Underlying malignancy or endometrial hyperplasia should be considered and first-line biopsy is recommended [6]. It is also important to assess the risk of sarcoma, although this may be very challenging preoperatively [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…demonstrated that regardless of the embolic material used, pedunculated serosal fibroids were less likely to infarct than transmural tumours [23]. Thus, while the embolization of pedunculated fibroids may be safe, the chance of successful treatment may be lower compared with fibroids in other uterine locations [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations